Seismic evidence of extensive microbial gas migration and trapping in submarine gas hydrates (Rakhine Basin, Bay of Bengal). (March 2023) - Foschi, M.; Etiope, G.; Cartwright, J.A.
Abstract: Submarine methane-rich gas hydrates in ocean sediments are a potential atmospheric greenhouse gas and energy source. It is considered that microbial methane is generally autochthonous, produced in situ within the gas hydrate stability zone with low gas flux and pressure, while thermogenic gas is allochthonous, migrated from a deeper petroleum system, with higher gas flux and pressure and therefore potentially higher energy resource and environmental impact. Here, we report on the allochthonous nature of large microbial gas hydrate deposits in the Rakhine Basin, Bay of Bengal. An innovative and automatic tool, developed to analyze high-resolution three-dimensional seismic data, allowed to detect hundreds of thousands gas occurrences throughout a 2 km thick Pliocene-Pleistocene sedimentary sequence extending below the gas hydrate stability zone. A supercharged section matching the present-day optimum temperature for microbial methanogenesis was identified. Combining seismic and geochemical data of the Rakhine Basin gas system points to a dominant microbial nature of the gas. Stacked amplitude anomalies and vertical anomaly clusters demonstrate active free-phase gas migration towards the shallow gas hydrate stability zone. The Rakhine Basin gas hydrates are the ultimate seal for the entire petroleum system and represent a case of "frozen seepage" of microbial gas with relatively high flux and pressure. Highlights: Seismic evidence of allochthonous microbial methane in gas hydrates in the Bay of Bengal. Hundreds of thousands gas occurrences along advective migration paths define the active microbial gas kitchen. Submarine gas hydrates seal the upward gas migration.